PENGARUH LATIHAN AKSELARASI TERHADAP KECEPATAN LARI 100M PADA MAHASISWA PUTRA KEPELATIHAN 1A - Febri Binatalisa; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : A problem research was “is there any effect of akselarasi on the running speed 100m of the student sport coaching man 1a”. A type of this research was experiment research by using a sempling total technique 12 peopel semple was taken the research data was obtained and collected by a pree test and pots test of running 100m. The result of data was obtained and analyzed statistically, so the tets of hypotesisi had been proposed based on the problem “ there is an effect of akselarasi (x) on the running speed 100m of the studet sport coaching man 1a(y). Bsed on the vaule- test analisis as 2,093 and t table as 1,769 means t vaule > t table. Soit be councluded that Ha is accepted and Ho is rejected. In line with explanation above, it can be stated that there is any sgnifican effect of akselarasi on the running speed 100m of the student sport coaching man 1a.Keyword : Akselarasi, Speed Run